HUBUNGAN ANTARA BERAT BADAN SAPI BETINA PERANAKAN ONGOLE DAN SAPI PERSILANGAN PADA TINGKATAN UMUR YANG BERBEDA TERHADAP UKURAN DAN KARAKTERISTIK OVARIUMNYA - Iqbal Hamdani, M. Dima (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
The aim of the research is to know about Correlation between Ongole Crossbreed and CattleCrossbreed Bodyweight in the different age level for the size and Characteristic of ovary. In thisexperiment, Ongole Crossbreed and Cattle Crossbreed divided into two different age level group,Age level >4 years and Age level <4 years, also 40 Ovary right and Ovary left. The research wasconducted in the commercial slaughterhouse in Metro and East Lampung. The results indicatebreed have correlation with Bodyweight. Right Ovary have more weight than Left Ovary.Correlation positive between bodyweight and left ovary of Ongole Crossbreed andCattle Crossbreed in Age level<4 years and >4 years and correlation negative betweenbodyweight with right ovary of Ongole Crossbreed <4 years and >4 years. Correlation betweenbodyweight of Cattle Crossbreed with Right Ovary is 0,97